Islamic Religious Education for Sustainable Development Goals (SDGs): Promoting Sustainability Values in Educational Settings in Turkey - Gunbay (Muaddib: Jurnal Pendidikan Agama Islam, 2024)
The growing global concern regarding environmental degradation, social inequality, poverty, climate change, and sustainable economic development has intensified the importance of education in achieving the Sustainable Development Goals (SDGs). Educational institutions are increasingly expected to cultivate sustainability awareness, ethical responsibility, and behavioral transformation among students. In Turkey, where Islamic values continue to influence educational and social life, Islamic Religious Education (IRE) offers significant potential for supporting sustainability-oriented learning by integrating moral, ethical, social, and environmental dimensions aligned with the SDGs. This study explores the role of Islamic Religious Education in promoting sustainability values within educational settings in Turkey and examines its contribution to achieving the Sustainable Development Goals. Using a qualitative literature review approach, the study analyzes scholarly publications, educational reports, and theoretical discussions concerning Islamic education, sustainability, and SDGs implementation. The findings indicate that Islamic Religious Education positively contributes to sustainability awareness through teachings emphasizing stewardship (khalifah), justice (adl), moderation (wasatiyyah), compassion (rahmah), and social responsibility. Islamic educational practices support student understanding of environmental conservation, social equity, poverty reduction, ethical consumption, and community engagement, aligning closely with multiple SDGs objectives. However, challenges remain, including curriculum limitations, insufficient teacher preparedness, weak interdisciplinary integration, and varying institutional capacities. The study concludes that Islamic Religious Education can serve as an effective educational platform for promoting sustainability values and supporting SDGs achievement in Turkey when accompanied by curriculum innovation, teacher training, and stronger integration between religious ethics and sustainability education.